Analysis of the Effect of Potassium of Young Coconut Water Consumed by Pregnant Women in the Third Trimester on the Levels of Potassium Saliva of Mothers and the Newborn as well as Meconium Levels of Amniotic Fluid as an Indicator of Meconium Staining (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Meconium staining of amniotic fluid harms newborns. Pregnant women in Palangka Raya City have the habit of consuming young coconut water to prevent the meconium staining of amniotic fluid. Young coconut water contains the highest mineral potassium. Potassium can affect the intestinal peristaltic.Objective: Analyzing the effect of potassium of young coconut water consumed by pregnant women in the third trimester on the levels of potassium saliva of mothers and the newborn and meconium levels of amniotic fluid.Methods: This study was a prospective cohort study of third-trimester pregnant women. The study sample was taken randomly, 24 pregnant women who consumed young coconut water and 24 who did not consume young coconut water.Results: Potassium levels of young coconut water had a positive correlation with levels of maternal salivary potassium (b = 0,414, p = 0,000). Maternal salivary potassium levels had a negative correlation with meconium levels of amniotic fluid (b = -0,603, p = 0,000). Maternal salivary potassium levels through infant salivary potassium levels had a negative correlation with meconium levels of amniotic fluid (b= -0,205, p = 0,000).Conclusion: Young coconut water consumed by pregnant women during the third trimester can prevent the meconium staining of amniotic fluid
Keywords: Potassium, young coconut water, pregnant women, meconium